miR-17-5p regulates endocytic trafficking through targeting TBC1D2/Armus - Serva, Andrius; Knapp, Bettina; Tsai, Yueh-Tso; Claas, Christoph; Lisauskas, Tautvydas; Matula, Petr; Harder, Nathalie; Kaderali, Lars; Rohr, Karl; Erfle, Holger; Eils, Roland; Starkuviene-Erfle, Vytaute (PLOS ONE, 2012)
miRNA cluster miR-17-92 is known as oncomir-1 due to its potent oncogenic function. miR-17-92 is a polycistronic cluster that encodes 6 miRNAs, and can both facilitate and inhibit cell proliferation. Known targets of miRNAs encoded by this cluster are largely regulators of cell cycle progression and apoptosis. Here, we show that miRNAs encoded by this cluster and sharing the seed sequence of miR-17 exert their influence on one of the most essential cellular processes - endocytic trafficking. By mRNA expression analysis we identified that regulation of endocytic trafficking by miR-17 can potentially be achieved by targeting of a number of trafficking regulators. We have thoroughly validated TBC1D2/Armus, a GAP of Rab7 GTPase, as a novel target of miR-17. Our study reveals regulation of endocytic trafficking as a novel function of miR-17, which might act cooperatively with other functions of miR-17 and related miRNAs in health and disease.
Gesehen am 13.07.2018